Evaluation of surgical outcome of Jack vertebral dilator kyphoplasty for osteoporotic vertebral compression fracture—clinical experience of 218 cases. Issue 1 (December 2016) - Fan, Jin; Shen, Yimin; Zhang, Ning; Ren, Yongxin; Cai, Weihua; Yu, Lipeng; Wu, Naiqing; Yin, Guoyong
Abstract Background Osteoporotic vertebral compression fracture is a serious complication of osteoporosis. Various vertebral kyphoplasty surgeries, which have their own unique features, are commonly used for osteoporotic vertebral compression fracture. Based on the anatomic property of the thoracolumbar vertebral pedicle that its horizontal diameter is twice that of the vertical diameter, we designed Jack vertebral dilator for better restoration of the vertebral height by manipulating the mechanical force. Methods A total of 218 patients (236 vertebrae) with osteoporotic vertebral compression fracture were treated with Jack vertebral dilator. Surgery was successfully completed in all cases, and all the 218 patients were followed up for an average of 14.2 months (range 3 to 30 months). Results Bone cement leakage occurred in 12 cases, but no symptoms were reported. No other complications were noticed. The VAS scores were 8.2 ± 1.3, 1.7 ± 0.9, and 1.8 ± 0.8 and the ODI was 78.2 ± 13.3 %, 18.5 ± 7.3 %, and 20.9 ± 6.8 % before surgery and 1 week after surgery and at the final follow-up, respectively. The anterior vertebral body height was 19.3 ± 3.2, 25.1 ± 2.6, and 24.9 ± 2.6 mm and the central vertebral body height was 18.7 ± 3.0, 24.8 ± 3.0, and 24.5 ± 2.9 mm before surgery and 1 week after surgery and at the final follow-up, respectively. Cobb angle was 16.2° ± 6.6°, 8.1° ± 5.6°, and 8.5° ± 5.6° before surgery and 1 week after surgery and at the final follow-up, respectively. Conclusions Jack vertebral dilator kyphoplasty for osteoporotic vertebral compression fracture is safe, feasible, and effective and has the prospect of further broad application in the future.